Larval Development of the New Zealand Mussel Perna canaliculus and Effects of Cryopreservation - Rusk, Adam Brett (Auckland University of Technology, 2012)
The New Zealand green-lipped mussel, Perna canaliculus, is an important aquaculture species. This commercially attractive mussel species contributes over 70% of total aquaculture in New Zealand, with exports in excess of $NZ 220 million. This industry relies heavily on wild-caught spat, which accounts for about 80% of seed requirements in mussel farming. This source of wild spat is unreliable and unpredictable. As a consequence, recent research focus has been directed at successfully rearing larvae to spat within hatchery settings. Previous research has been focussed at achieving high settlement rates, but this is highly variable due to seasonal variations and inconsistent rearing parameters. An alternative approach to utilising seasonally viable larvae is to cryopreserve (freeze) healthy Perna canaliculus larvae and thaw them on demand for hatchery production. This allows a year-round spat supply without the need to condition broodstock for out of season production. However, the success of this method also has been variable, often resulting in low survival rates. Part of the reason for this lack of success is that little is known about the thawing and post-thawing effects on larval viability and subsequent development. Overall, knowledge about the intricate developmental processes involved within the embryo or larval stages is lacking, and no detailed study has characterised these stages of larval development. Therefore, this study is the first to describe, in detail, larval development of Perna canaliculus from embryogenesis through to settlement in a hatchery environment. This project also included the first comprehensive investigation of the effects of cryopreservation for post-thawed trochophore (16 hours post-fertilisation) and D-stage (48 hours post-fertilisation) larvae through subsequent larval development. A multi-technique approach involving visual observations, scanning electron microscopy, histology, and immunochemistry were performed on larval samples collected daily through all stages of larval development over a 21-day rearing period. Cryopreserved and normal larvae were assessed daily through survivability, shell length, feeding consumption, shell morphology, organogenesis, and neurogenesis. Normally reared larvae had decreasing percent survival with the lowest survival values occurring at the pediveliger and post-settlement stage. Feeding consumption also varied over the 21-day rearing time period with a typically high feeding rate up to 15 days post-fertilisation to metamorphosis. Shell length was positively linear with little deviation except near the settlement stage where variations in shell growth were apparent. A low larval density (< 4%) was observed through to settlement and substrate attachment stages, which normally indicates competent settlement behaviour. For these normally reared larvae, embryogenesis was followed to a gastrula stage at 18 hours post-fertilisation, with the appearance of a blastopore, apical sense organ, and enclosing vegetal pole. D-stage larvae had limited organogenesis with the development of an alimentary and nervous systems. Shell morphology on D-stage larvae (2 days old) revealed a flat hinged, pitted punctuate prodissoconch I shell, followed closely by commarginal growth lines within the prodissoconch II shell at 4 days old. The umbo stage (7–17 days old) had further organogenesis development with a protruding beating velum, a well-developed posterior and adductor muscle, velum retractor muscles, and further dissoconch II secretion of the shell with a more rounded umbonate appearance. Neurogenesis had significantly progressed at this stage with paired cerebral, pedal, and visceral ganglia observed. Pediveliger larvae (18 days old) developed a complete nervous system with more innervations and fibres extending throughout the larva. During pediveliger development, a rapid metamorphosis transition occurred with the development of a gill rudiment, eye spot, and functioning foot. The first appearance of a dissoconch shell layer appeared during this transition. Within the cryopreservation study, results showed that there were significant differences in survivability, shell length, and feeding consumption between controls (not cryopreserved) and frozen (cryopreserved) treatments, but no comparable differences were observed among both frozen treatments (cryopreserved at the trochophore stage and cryopreserved at the D-stage) throughout the 21-day development period. At 18 days post-fertilisation, ~23% of control larvae had progressed to competent pediveliger, while <1% of both frozen larvae stages survived. Those larvae that survived were unable to develop to competent pediveliger or post-larvae. Settlement was achieved in ~9% of control larvae at 21 days post-fertilisation with most individuals developing eye spots. Significant differences were observed in neurogenesis between frozen trochophore larvae and controls. Conversely, frozen D-stage larvae did not differ greatly to controls, and differed slightly to trochophore larvae. Characterisation of shell morphology revealed abnormalities to larvae on both frozen treatments. Frozen trochophore larvae showed the greatest shell abnormalities, which suggests that cryo-damage to the shell gland had occurred. Organogenesis was delayed in larvae within both frozen treatments with no larvae within frozen treatments developing an eye spot. However, larvae in controls successfully made the transition to settlement. This delay in organogenesis and overall developmental characteristics were indicative of cryo-injuries sustained at a cellular level. The relevance of this work ultimately fills existing gaps in larval development of Perna canaliculus in normal and cryopreserved larvae. Characterisation of both viable and abnormal larvae through development is of benefit in reducing commercial hatchery costs and understanding the biology of Perna canaliculus larvae.
Keywords: Larval development; Cryopreservation; Organogenesis; Neurogenesis; Shell morphology